1994
DOI: 10.1093/oxfordjournals.eurheartj.a060433
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the mechanism of pressure related atrial fibrillation

Abstract: In order to investigate the effect of atrial pressure on the propensity of the atria to fibrillate and the mechanism of this association, the right atrial pressure was changed acutely by transfusion-bleeding in 12 anaesthetized open-chest dogs. Under various atrial pressures the conduction time was measured between two pairs of hook electrodes positioned on the two atrial appendages respectively. The effective refractory period was measured by continuous pacing of the right atrium at a 250 ms cycle length at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 2 publications
(3 reference statements)
3
20
0
1
Order By: Relevance
“…6,22,24 In a canine model of progressive heart failure, interstitial fibrosis and heterogeneous conduction were considered important determinants of the substrate for AF. 14 In human studies as well, atrial dilatation and impaired conduction were correlated with atrial arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…6,22,24 In a canine model of progressive heart failure, interstitial fibrosis and heterogeneous conduction were considered important determinants of the substrate for AF. 14 In human studies as well, atrial dilatation and impaired conduction were correlated with atrial arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Studies of human atrial electrophysiology performed in the electrophysiology laboratory have focused on RA refractoriness in patients without structural heart disease. These studies demonstrated variable results, including no change in ERP, 7 a reduction in ERP, 8 and an increase in ERP.…”
Section: Acute Atrial Stretch and Conduction Blockmentioning
confidence: 99%
“…This can be explained by the preservation of the sinus node integrity when the more recent techniques are used. Also, modifications in the atrial geometry predispose to atrial arrhythmias, as well as to increased internal pressure, since these events prolong the electric conduction time 34,54,55 . An additional risk for arrhytmias are the acute graft rejection episodes 34,56 .…”
Section: Discussionmentioning
confidence: 99%